Ovariectomy Impairs Socio-Cognitive Functions in Dogs - Anna Scandurra; Alessandra Alterisio; Anna Di Cosmo; Antonio D’Ambrosio; Biagio D’Aniello (Animals, 2019)
Recent studies have underlined the effect of ovariectomy on the spatial cognition of female dogs, with ovariectomized dogs showing a clear preference for an egocentric rather than an allocentric navigation strategy whereas intact females did not show preferences. Intact females had better performances than gonadectomized females in solving a learning task in a maze. Ovariectomy also affects socio-cognitive abilities, reducing the dog’s level of attention on the owner. We tested dogs (Canis lupus familiaris) in the object choice task paradigm to assess whether an ovariectomy could impair females’ ability to follow human signals. Forty pet dogs (18 intact females (IF) and 22 gonadectomized females (GF)) were tested in the object choice task paradigm using the human proximal pointing gesture. For the analysis, the frequency of correct, wrong and no-choices was collected; moreover, the latency of the correct choices was also considered. The IF group followed the pointing gestures more often than the GF group and with a lower latency, whereas a significantly higher no-choice frequency was recorded for the GF group. These results show a detrimental effect of ovariectomy on dogs’ socio-cognitive skills related to the responsiveness to human pointing gestures.